Addressing crop interactions within cropping systems in LCA - Goglio, Pietro; Brankatschk, Gerhard; Trydeman Knudsen, Marie; Williams, Adrian G.; Nemecek, Thomas (Springer, 2017)
Purpose The focus of the Life Cycle Assessment (LCA) of an agricultural plant product is typically on one crop. However, isolating one crop from the cropping system that it belongs to is often challenging because the crops are often interlinked with the other crops in the cropping system. The main objectives of this discussion article are: i) to discuss the characteristics of cropping systems which might affect the LCA methodology, ii) to discuss the advantages and the disadvantages of the current available methods for the life cycle assessment of cropping systems and iii) to offer a framework to carry out LCA of crops and cropping systems. Methods The definition of cropping systems is provided together with a description of two types of LCA: product LCA and system LCA. The LCA issues related to cropping systems characteristics have been classified as 1) crop interrelationship, 2) crop management and emissions, and 3) functional unit issues. The LCA approaches presented are: Cropping System, Allocation approaches, Crop-by-Crop approach, Combined approaches. The various approaches are described together with their advantages and disadvantages, applicability, comprehensiveness and accuracy. Results and discussion The Cropping System approach is best suited for system LCA. For product LCA, none of the methods is fully exhaustive and accurate. The crop sequence approach takes into consideration cropping systems issues if they happen within the year or season and cannot be applied for intercropping and agroforestry systems. The allocation approaches take into consideration cropping system effects by establishing a mathematical relationship between crops present in the cropping systems. The Model for integrative Life Cycle Assessment in Agriculture (MiLA) approach considers cropping systems issues if they are related to multiproduct and nutrient cycling; while the Crop-by-Crop approach is highly affected by assumptions and considers cropping system issues only if they are related to the analysed crop. Conclusions Each LCA approach presents advantages and disadvantages. For system LCA, the Cropping Systems approach is recommended. For product LCA, environmental burdens should be attributed applying the following hierarchy: 1) attributed to the crop if based on a clear causality; 2) attributed with combined approaches and specific criteria; 3) attributed with allocation approaches and generic criteria. These approaches should be combined with the Cropping System approach.
Keywords: Allocation; Crop; Cropping systems; Cropping systems characteristics; LCA; Methods; Product LCA; System LCA